The Many‐Worlds Interpretation of Risk Neutrality. Issue 105 (17th January 2020) - Brown, Aaron
Abstract : There are many risk‐neutral worlds, with different probabilities that support the same market prices. This matters in understanding how the originators of the Black‐Scholes model each thought differently about how the math linked to the economics…